2009
DOI: 10.3168/jds.2008-1757
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of serum protein removal from skim milk with ceramic and polymeric membranes at 50°C

Abstract: Raw milk (2,710 kg) was separated at 4 degrees C, the skim milk was pasteurized (72 degrees C, 16 s), split into 3 batches, and microfiltered using pilot-scale ceramic uniform transmembrane pressure (UTP; Membralox model EP1940GL0.1microA, 0.1 microm alumina, Pall Corp., East Hills, NY), ceramic graded permeability (GP; Membralox model EP1940GL0.1microAGP1020, 0.1 microm alumina, Pall Corp.), and polymeric spiral-wound (SW; model FG7838-OS0x-S, 0.3 microm polyvinylidene fluoride, Parker-Hannifin, Process Advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
163
12
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(200 citation statements)
references
References 24 publications
24
163
12
1
Order By: Relevance
“…These membranes have a decreasing permeability built into either the external surface of the support structure (GP membranes) or selective layer (Isoflux) on the inside of the flow channels. The comparative studies (Zulewska et al, 2009;Adams and Barbano, 2013) carried out in our laboratory showed differences in membrane selectivity and process yield when processing skim milk with different ceramic modules. In general, UTP system showed best SP passage, followed by GP and Isoflux membranes.…”
Section: Introductionmentioning
confidence: 95%
“…These membranes have a decreasing permeability built into either the external surface of the support structure (GP membranes) or selective layer (Isoflux) on the inside of the flow channels. The comparative studies (Zulewska et al, 2009;Adams and Barbano, 2013) carried out in our laboratory showed differences in membrane selectivity and process yield when processing skim milk with different ceramic modules. In general, UTP system showed best SP passage, followed by GP and Isoflux membranes.…”
Section: Introductionmentioning
confidence: 95%
“…The interest in separation by the use of inorganic membranes has rapidly increased during the last two decades. Due to their potential application in a wide range of industrial processes such as water and effluent treatments [1][2][3][4][5], drink clarification [6][7][8], milk pasteurisation [9][10][11][12][13], biochemical processing [14,15], inorganic membrane technologies have achieved an increasing importance. Ceramic membranes have many known advantages such as high thermal and chemical stability, pressure resistance, long lifetime, and catalytic properties from their intrinsic nature [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Do redukcji tłuszczu w produktach wytwarzanych na bazie białek serwatkowych stosuje się różne metody. Najczęściej jest to wirowanie oraz techniki membranowe [4,7,22]. Stosunkowo nowym sposobem jest zastosowanie chitozanu, który wiąże tłuszcz i barwnik (np.…”
Section: Właściwości Pianotwórcze Koncentratów Białek Serwatkowych O unclassified